Diário de leituras: um instrumento de alfabetização e letramento em turmas do ensino fundamental - Ferreira de Almeida, Mabelle (2024)
I will present, in this article, a reflection on the Diary of Readings as a pedagogical tool and analysis of the results of a practice developed with students of the sixth year of elementary school that I intended, from the reading of the literary narrative “When my father lost his job (Wagner Costa)”, to verify the involvement they would establish with the work, thus contributing to the formation of readers. The methodology used was writing in reading diaries that intended to enable the exercise of authorial writing, the records of readings of the literary text and writing to verify the relationship with the narrative. This procedure allowed a reflection on the diaries and subjectivity in reading. For that, I turned to authors such as Anna Rachel Machado (1998), Yunes (2003) and Rangel (2003), among others, who contribute to thinking about the teaching of literature and the formation of readers. Finally, after observing the written productions and analyzing them, I will present some results that I will share in this text.   Keywords: Reading diary. Literary reading. Pleasure in reading.